A method of measuring weak-charge of self-powered sensors based on triboelectric nanogenerator. (May 2022) - Lei, Wenqian; Lu, Shan; Wang, Qi; Yuan, Pengfei; Yu, Hua
Abstract: Although most the triboelectric nanogenerator sensors use the output voltage signal as the sensing signal, other signals such as current or charge cannot be ignored as sensing signal. TENG sensor is equivalent to a charge source with variable internal capacitance and outputs weak charge signal, which is not convenient for direct application as sensing signal. Therefore, it is essential to study the processing method of the output charge of TENG sensor. In this paper, a preprocessing method based on the output charge signal of TENG sensor is proposed to achieve accurate measurement of weak charge. In order to measure the amount of charge transfer output by the TENG device, the characteristics of "virtual ground"(non-inverting terminal grounding) at the inverting input of the inverting operational amplifier is used to transfer the charge signal output by the TENG sensor to the feedback arm capacitor, and the output charge signal is measured by measuring the low impedance and low voltage signal output by the inverting operational amplifier. Then, the reason affecting the characterization accuracy of the preprocessing method is analyzed theoretically, and the optimization strategy of each component parameter is established. Experiments are carried out with contact-separated mode triboelectric nanogenerator (CS-TENG) and rotary triboelectric nanogenerator (R-TENG) respectively, and the errors of the preprocessing method are controlled within 7% and 5% respectively, which proves the feasibility of the preprocessing method. This provides a new way to extract the charge signal from TENG sensor and is expected to be a new method to characterize the charge signal in TENG energy harvester. Graphical Abstract: ga1 A preprocessing circuit based on the output charge signal of TENG sensor is proposed. Using the characteristics of "virtual ground" at the inverting input of the inverting operational amplifier, the charge signal output by TENG sensor is transferred to the feedback arm capacitance, and the output charge signal is measured by measuring the low impedance and low voltage signal output by the inverting operational amplifier. The charge measurement scheme can easily measure TENG output signal, and has high measurement accuracy without damaging the waveform. This provides a new way to extract the charge signal from TENG sensor and is expected to be a new method to characterize the charge signal in TENG energy harvester. Highlights: This proposed method solves the inconvenience of characterization when the charge signal of TENG sensor. The reason affecting characterization accuracy of circuit is analyzed, and the optimization strategy of component parameters is established. The proposed circuit is also expected to be a new universal method for characterizing charge signals for different kind of TENG.